2013
DOI: 10.1097/smj.0b013e31828de4a4
|View full text |Cite
|
Sign up to set email alerts
|

Parental Perspectives of Diabetes Management in Alabama Public Schools

Abstract: The accommodation and care for children with diabetes is highly variable within much of the Alabama public school system. The ability to conveniently check BGLs at school is key for participation in all school activities and for parental satisfaction with diabetes care at school. Institution of a uniform, statewide diabetes training protocol for school personnel could improve care and parental satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…The parents expressed concern about the quality of care when a school nurse is not present (one nurse works in a few schools). Many parents believe that the constant presence of a nurse in school should improve the situation ( 15 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The parents expressed concern about the quality of care when a school nurse is not present (one nurse works in a few schools). Many parents believe that the constant presence of a nurse in school should improve the situation ( 15 ).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, parents were examined by Amilltegui et al, Driscoll et al, Hellems & Clarke, Schmidt et al and Skelley et al ( 3 , 7 , 10 , 15 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Differences in parents' and nurses' perceptions regarding adherence to 14 recommendations published by the American Diabetes Association about care of children specifically in the school environment have been documented . In addition, studies have identified parental concerns about lack of teacher involvement , parental and children's concerns about lack of availability of nursing staff on a daily basis , dissatisfaction with/lack of confidence in diabetes management at school , and children's and parents' desires for improved diabetes knowledge among a variety of school staff [e.g., teachers, cafeteria staff; ]. Finally, teachers' desires for better training have also been documented .…”
mentioning
confidence: 99%